Young People and Trade Unions: New Challenges for a Generational Change - Castiglioni, Giovanni (Richtmann Publishing, 2012)
The relationship between young people and trade unions is fundamental for labour organisations because it isincreasingly necessary to re-think their generational change. The article aims to deepen understanding of the new challengesconcerning youth and trade unions by reflecting on the labour organisations’ renewal and analysing how they could involveyoung generations. Trade unions need to establish networks among young people both inside and outside the labourorganisations and, at the same time, deal with young workers in contexts external to the workplace, reaching out to youthgenerations through innovative experiences and new models of aggregative participation. Ultimately, the new tasks that will beimportant to the future of labour organisations include investing in new generations and also accompanying providing themassistance in particular moments of insecurity, such as the transition from school to work or during unemployment; and helpingthem to develop their job skills. The analysis of the essay focuses on how trade unions can apply strategies and policies tosupport initiatives and social proposals that could facilitate young workers’ participation in trade unions.